The Significancy of Immediate Enactment of the Draft of Indonesian Criminal Code (RKUHP) to Ensure Judge’s Full Compliance with Article 5 (1) of Law No. 48 of 2009 on Judicial Authority - Yuber Lago (LPPM Universitas Terbuka, 2022)
The Criminal Code that is currently applied in Indonesia is a product of colonialism law which originates from the Dutch Wetboek van Strafrecht voor Nederlands Indie and has been adopted since 1918. In its article 1 paragraph (1) stipulates legality principle; that no action can be punished unless with a pre-existing criminal law provision. However, the Article 5 paragraph (1) of the Law No. 48 of 2009 stipulates that a judge must delve, follow, and understand the living legal norms and values that are felt by the society. These living norms and values are not written and most certainly not enacted unlike the written law. However, they are crucial in upholding community’s sense of justice, and the Law on Judicial Authority has obliged judge to pay great attention to those values. In the Draft, the living laws are accommodated in its article 2 and article 12(2). This study examines the importance to immediately enact the Draft to help realizing judge’s ideal as stipulated in Article 5. The researcher employed a normative juridical method through a statutory approach to study the ratio legis of the laws. Furthermore, the researcher applied qualitative analysis. The result of this study finds out that the Draft accommodates the living law of society better, and therefore the Government shall enact it immediately, with all things considered.